APLIKASI PUPUK ORGANIK, NPK DAN BPF PADA ULTISOLS UNTUK MENINGKATKAN C-ORGANIK, N-TOTAL, SERAPAN N DAN HASIL JAGUNG MANIS (Zea mays saccharata Sturt.) - Anni Yuniarti; Yuliati Machfud; Mita Mita (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
This research was conducted to find out the interaction of organic fertilizer, NPK with BPF on Ultisols of the organic carbon, total nitrogen, N uptake, and result of sweet corn (Zea mays saccharata Sturt). The research was conducted from June to September 2013 at the Experimental Ciparanje, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang, West Java elavated at 724 meters above sea level. The experimental design used was Randomized Block Design (RAK) arranged in factorial pattern with 14 treatments and three replicates. The first factor is organic and NPK fertilizers (P) consisting of seven levels : without organic fertilizer and NPK; POPG + ½ dose of NPK; POPG + 1 dose of NPK: Compost + ½ dose of NPK; Compost + 1 dose of NPK; Manure + ½ dose of NPK; Manure + 1 dose of NPK. The second factor is the Solvent of phosphoric Bacteria (B) consisting of two levels : without the BPF and BPF 10 mL The results of experiment showed that there was not interaction effect between different called organic fertilizer and NPK with BPF of organic carbon, total nitrogen, plant uptake of N, and results of sweet corn. Independently organic fertilizer, NPK gave significant effect on organic carbon, total nitrogen, plant uptake of N, results of sweet corn and BPF was significant effect of organic carbon and plant uptake of N but has not siginificant effect of total nitrogen and results sweet corn. Treatment POPG with 1 dose of NPK shows the best formulations can improve results of sweet corn on Ultisols Jatinangor, that is 249,17 g plant-1 or 9 t ha-1.